Evaluation of the use of Electronic Portfolios in Initial Teacher Training (Educational Knowledge, 2017)
In the context of the Knowledge Society, it is essential that future teachers master information and communication technologies (ICTs) to meet the needs of learners in the new millennium. The objective of this research was to determine how Physical Education students value the use of electronic portfolios. The methodology was qualitative, descriptive, and phenomenological. Initially, information was gathered through a focus group and interviews, which were then used to develop a semi-structured survey. The final participants were a homogeneous group of 56 students in their final two years of study.The results reveal factors they value when using the portfolio, such as: exchanging ideas, resolving doubts, and reviewing work produced by themselves and their peers. They also expressed dislikes regarding aspects of the software design, system capacity, and the visibility of their information in internet search engines. It is concluded that students highly value the use of portfolios, which may encourage their willingness to work with technology once they become teachers.
Keywords: electronic portfolio; initial teacher training; competence assessment; Information and Co- munication Technologies